School Principal Leadership Style In Improving Teacher Professionalism - Nuswantoro, Patriandi; Marsinah, Marsinah; iqbal , Muhammad; Elvi Rahmi; Muhammad Bambang Purwanto (International Journal of Technology and Education Research, 2023)
This study generally aims to determine the leadership style of school principals in increasing the professionalism of teacher performance at SMK PGRI 1, Semarang City. The approach used in this study is a qualitative approach, with data collection techniques through observation, interviews, and documentation studies. The research subjects were school principals, teachers, school committees, and students at SMK PGRI 1 in Semarang City. The results of the study can be explained as follows: (1) the principal's leadership style is inferred from eight aspects that the researcher has determined, namely: (a) the daily behaviour of the principal shows an attitude of concern, openness, cheerfulness, firmness, wisdom, discipline and commitment and has emotions stable; (b) the delegation of tasks is carried out in a fair manner and the provision of direction; (c) decision making is carried out jointly/consensus; (d) supervision carried out by directly monitoring progress; (e) school development includes the development of school facilities and infrastructure, extracurriculars, learning and teachers and education staff; (f) open and two-way communication using clear and easy-to-understand language; (g) motivation by giving encouragement/enthusiasm and meeting the needs of all school personnel and (h) rewards in the form of praise and thanks. in leading the principal using a group leadership style. So that it can be understood that in an effort to improve the performance of teachers and education staff, the principal empowers them, develops their competence, and provides motivation and awards; (2) the factors that influence group leadership style are: (a) the leader himself has personality, past experience, and high expectations for all school personnel to develop the school; (b) the characteristics of superiors who prioritize the task implementation process; (c) the characteristics of subordinates who show enthusiasm and willingness to change; (d) task requirements by providing guidance regarding task clarity; (e) organizational climate and policies can help improve the quality of human resources in the school environment